Social determinants associated with health care access in children under 6 years of age from a public health network in Santiago de Cali: a multilevel analysis - Lina María García-Zapata; Gustavo Bergonzoli (Universidad de Antioquia, 2017)
Introduction: a public health services network in Cali, Colombia, implemented the Family Health Strategy (FHS) for 1000 low-income families. The objective of this study was to identify the effects of individual and contextual variables as determinants in consultations made for children under six years of age, for Acute Diarrheal Disease (ADD), Acute Respiratory Infection (ARI), and dental cavities. Methods: the household environment was the unit of analysis and the mother was the information source. A multivariate multilevel linear regression analysis was performed to assess how contextual and individual variables determine medical care. The response variable was the number of consultations provided to children by the public health network. The effects of fixed and random variables were estimated to assess the variation in the number of consultations across census tracts. Results: in the first-level explained variance, age contributed a 6.3% in ADD consultations, and the child's sex contributed 5.3%, while having a pet at home contributed 9% in the second-level explained variance. In ARI consultations, the parents' educational level contributed 3.5%, the materials used for home roofs contributed 20.7% and the population type 33%, for a total contribution of 57.2%. The child's age explained 9.4% in dental cavity consultations, while overcrowding and tobacco use at home accounted for 53% of variability at the second level. Conclusions: the social and environmental determinants of each household accounted for over 50% of the variability in medical consultations provided to children under the age of six.